Prolonged elevation of intraocular pressure results in retinal ganglion cell loss and abnormal retinal function in mice. (January 2015) - Khan, A. Kareem; Tse, Dennis Y.; van der Heijden, Meike E.; Shah, Priya; Nusbaum, Derek M.; Yang, Zhuo; Wu, Samuel M.; Frankfort, Benjamin J.
Abstract: The purpose of this study was to assess the impact of prolonged intraocular pressure (IOP) elevation on retinal anatomy and function in a mouse model of experimental glaucoma. IOP was elevated by anterior chamber injection of a fixed combination of polystyrene beads and sodium hyaluronate, and maintained via re-injection after 24 weeks. IOP was measured weekly with a rebound tonometer for 48 weeks. Histology was assessed with a combination of retrograde labeling and antibody staining. Retinal physiology and function was assessed with dark-adapted electroretinograms (ERGs). Comparisons between bead-injected animals and various controls were conducted at both 24 and 48 weeks after bead injection. IOP was elevated throughout the study. IOP elevation resulted in a reduction of retinal ganglion cell (RGCs) and an increase in axial length at both 24 and 48 weeks after bead injection. The b-wave amplitude of the ERG was increased to the same degree in bead-injected eyes at both time points, similar to previous studies. The positive scotopic threshold response (pSTR) amplitude, a measure of RGC electrical function, was diminished at both 24 and 48 weeks when normalized to the increased b-wave amplitude. At 48 weeks, the pSTR amplitude was reduced even without normalization, suggesting more profound RGC dysfunction. We conclude that injection of polystyrene beads and sodium hyaluronate causes chronic IOP elevation which results in phenotypes of stable b-wave amplitude increase and progressive pSTR amplitude reduction, as well as RGC loss and axial length elongation. Highlights: We studied mice exposed to mildly elevated IOP for 24 or 48 weeks. We examined changes in RGC number, axial length, and the ERG. RGC loss and axial length increase are mild at both time points. B wave amplitude increases are similar at both time points. Positive STR reductions are mild after 24 weeks but severe after 48 weeks.